Analysis of reports published by The New York Times in social networks about the reality of Latin America in 2017 - Gonzales García, Carlos Ricardo (2020)
This research addresses the informative, interpretative and opinionated treatment that an important and influential international media, The New York Times (Spanish edition), provided about the reality of Latin America through its reports during 2017. To this end, it made use of the superstructure-level scheme developed by Teun van Dijk (1990) and the interpretative and categorical judgments proposed by Santamaría and Casals (2000) to analyze the stories published by the newspaper on the Internet through its social networks. Among the main findings, it was found that this newspaper highlights, in depth, the heroic effort of Latin Americans for internal peace in certain conflict zones, both in Mexico and Colombia. It also uses personal testimonies to denounce cases of espionage and the environment.